PEMBERDAYAAN KEWIRAUSAHAAN UNTUK ANAK TUNARUNGU DENGAN PEMBUATAN SELAI NANAS - Misnawati, Misnawati; Abdul Aziz; Anwarsani, Anwarsani; Siti Rahmawati; Petrus Poerwadi; Nirena Ade Christy; Ibnu Yustiya Ramadhan; Yulina Mingvianita; Stefani Ratu Lestariningtyas; Syarah Veniaty (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
One of the aspirations that partners want is for deaf children to have an entrepreneurial spirit. Entrepreneurs have an important role in permeating business activities with an entrepreneurial spirit and turning that spirit into energy to engage in reforms, especially in the manufacture of pineapple jam. Deaf children are taught how to process, distribute, and market products. For this reason, through the Intellectual Product Business Development Program the "Educational" Campus will be given Entrepreneurship Empowerment Training for Deaf Children Through Making Pineapple Jam, in order to prepare deaf children in Palangka Raya to become independent individuals and able to do entrepreneurship through making pineapple jam. The targets achieved are (1) Enhancing Entrepreneurial Capability for Deaf Children Through Making Pineapple Jam; and (2) the production of a guide module for making pineapple jam for deaf children with a unique taste. The implementation of community service "Entrepreneurship Empowerment for Deaf Children Through Making Pineapple Jam," begins with an approach, then implementation in the field. After the implementation in the field, an evaluation is carried out, what are the obstacles faced in the training. Through these processes, it is hoped that the training can achieve the targets desired by partner one and partner two. Lastly, assistance was provided.